The illustrated Mahabharata a definitive guide to India's greatest epic - Pattanaik, Devdutt; Debroy, Bibek
Take a fresh look at India's great epic with The Illustrated Mahabharata and rediscover the lost kingdoms, dynasties, and characters of the Mahabharata. Follow the tale as it unfolds through 18 parvas with stunning photographs, paintings, sculptures, and historical artefacts. Discover the principal characters of the Mahabharata and their family trees, and understand key moments from the birth of Pandavas and Kauravas to the death of the elders. Know the Mahabharata with this beautiful retelling of India's greatest epic.